ICT-enabled technology delivery for sustainable horticulture - Padaria, R. N.; Mukherjee, Sweety; Ghosh, Bhaskar; Shravani, K.; Shravani, K.; Sarkar, Sujit; Sharma, Anamika; Singh, Bharat; Papnai, Gaurav (Indian Horticulture, 2025)
Digital technology is revolutionizing the dissemination of information for promoting sustainable horticulture, providing farmers with timely, region-specific, and actionable insights to improve crop management and resilience. Digital tools such as mobile applications, artificial intelligence (AI), drones, and community radio channels enable farmers to make data-driven decisions that optimize resources and enhance productivity. Mobile advisory platforms, like Pusa mKRISHI, deliver personalized, real-time support to farmers, guiding them in weather based crop care, pest management, and soil health practices, which collectively improve yield quality and reduce waste. This article presents several success stories illustrating the transformative impact of digital solutions on horticulture.For instance, KVK Gurugram’s drone-based spraying demonstrations covered 19 hectares and showcased 80-84% pest reduction in a range of horticultural crops, outperforming traditional methods. Similarly, Digital Green’s participatory video learning in Madhya Pradesh improved knowledge dissemination, leading to better adoption of agricultural practices. Community radio has emerged as avital platform for delivering localized agro-advisories, with data showing higher knowledge retention among listeners compared to non-listeners. Furthermore, the Pusa mKRISHI mobile advisory system exemplifies the importance of personalized, two-way communication in addressing farmers’ specific needs, enhancing decision making and resilience. Collectively, these initiatives demonstrate how digitalization in horticulture is paving the way for sustainable farming and increased profitability for small-scale farmers.